2017
DOI: 10.1038/s41598-017-13006-x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts support vascular growth through mechanical force

Abstract: The role of cancer-associated fibroblasts (CAFs) as regulators of tumor progression, specifically vascular growth, has only recently been described. CAFs are thought to be more mechanically active but how this trait may alter the tumor microenvironment is poorly understood. We hypothesized that enhanced mechanical activity of CAFs, as regulated by the Rho/ROCK pathway, contributes to increased blood vessel growth. Using a 3D in vitro tissue model of vasculogenesis, we observed increased vascularization in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 68 publications
(62 reference statements)
2
84
0
Order By: Relevance
“…1A). This suggested patient-derived ISEMFs are indeed capable of supporting vasculogenesis, similar to fibroblast cell types that have been explored in similar systems 7,10,11 .…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…1A). This suggested patient-derived ISEMFs are indeed capable of supporting vasculogenesis, similar to fibroblast cell types that have been explored in similar systems 7,10,11 .…”
Section: Resultsmentioning
confidence: 76%
“…The referenced Moya et al study involved co-culture of commercially available normal human lung fibroblasts and ECs embedded in fibrin gels adjacent to microfluidic media lines 7 . To date, other stromal populations such as mesenchymal stem cells and cancer-associated fibroblasts have been used in this system to support perfused capillary network formation via secreted and/or mechanical stimuli on ECs 7,10,11 .…”
mentioning
confidence: 99%
“…Other labs have demonstrated that although a stromal component featuring stromal cells or other support cells (pericytes, astrocytes, etc.) is necessary for the establishment of stable endothelial networks, specific stromal features, including their tissue source, expression of soluble factors, and mechanical activity, can inhibit or promote vascularization [67][68][69]. While increasing local presentation of VEGF within the GelMA hydrogel could increase the extent of the endothelial cell network formation, there is also potential to utilize endometrial-specific endothelial cells to create a tissue-specific model of endometrial angiogenesis and alter stromal cell decidualization status to determine the effects of stromal differentiation on endothelial network complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the up-regulation of PDGF-C was demonstrated as an alternative mechanism by which tumors presenting resistance to anti-VEGF-A therapy might promote angiogenesis [50]. In addition to soluble signaling factors, CAFs are also able to regulate vascular growth and may contribute to tumor neovascularization by their biomechanical behaviors, which differ from normal fibroblasts [51].…”
Section: Cafs Influence Other Components Of the Tmementioning
confidence: 99%